South Africa : Financial Sector Assessment Program-Reforms in the OTC Derivatives Market-Technical Note. (IMF Staff Country Reports; Country Report ;, 2015)
This Technical Note analyzes over-the-counter (OTC) derivatives market reforms in South Africa and identifies vulnerabilities that may potentially impact financial stability. South Africa is committed to reform its OTC derivatives market to reduce vulnerabilities and increase transparency. Reforms are being implemented through the Financial Market Act and Regulations for banks, reflecting the Basel III capital requirements. Swift progress on the consultation and issuance of FMA regulations, trade repository regulations, and related notices are warranted to proceed with reforming the OTC derivatives market. Secondary legislation still needs to be finalized and will contain requirements for financial market infrastructures.